Effect of personality traits and learning styles towards students’ academic achievement in Johor Bahru - Aqeel, Khan; Leong, Pyh Shin; Sanil, S Hishan; Mohamed Sharif, Mustaffa; Amalia, Madihie; Surena, Sabil (Science Publishing Corporation, 2018)
The purpose of this study is to investigate the effect of personality traits and learning styles towards the students’ academic achievement in Johor Bahru. A total of 101 students from IPG Kampus Temenggong Ibrahim were chosen to be part of the respondents with the use of simple random sampling. The instrument Big Five Inventory (BFI), Kolb’s Learning Style Inventory and The students’ academic achievement is measured through the Cumulative Grade Point Average, also known as CGPA. Descriptive statistics, Chi-Square Test, Spearman’s Correlation and Multiple Regression was used to anser research questions. The findings revealed that the most common personality traits displayed by the students are Openness and Conscientiousness while the most common learning style displayed by the students is Converger. The research also revealed that there is no significant effect of the combination of both the personality traits and learning style towards the prediction of the academic achievement among school students. The same goes to the difference of personality traits and learning style between male and female students was not significant as well